ESTUDO DA INCORPORAÇÃO DE FIBRAS DE REFORÇO E DO REAPROVEITAMENTO DE CARAPAÇAS CERÂMICAS NO PROCESSO DE FUNDIÇÃO POR CERA PERDIDA - Luis António Garcia de Sousa (2021)
Investment Casting is an ancient process to produce castings, being one of the most versatile and transversal processes in foundry. It has been used to produce any casting from the most delicate pieces of jewellery to the most complex components for the military or aerospace industry. There is, however, still a vast field for research and development in this world to improve the capacity of the process, making it more viable, economical, and profitable. This Master thesis addresses the main domains of the Investment Casting process, from the materials used to their processing to obtain the castings. The materials and techniques used in the production of the ceramic shells and the recovery methods of the refractories involved are focused. In a world where the environmental concern is always evident, the concept of Circular Economy is increasingly important, especially at the industrial level. In this sense, this work intends to analyse the effects of the use of sand resulting from the knockout of the ceramic shells recovered. The returns show some differences in particle size and chemical composition concerning the raw material used. There is a possibility of its incorporation promoting some deficiencies in terms of the process. The effects of the addition of ceramic fibres were analysed as an alternative to overcome these deficiencies, mainly in terms of mechanical strength. It was found that fibre-reinforced ceramic shells significantly increase their mechanical strength without any deterioration of other properties. The incorporation of a mixture of recycled sand and raw material turned out to be a success, without any apparent adverse effects on the quality and properties of the ceramic shells.